Leadership and management training for future-ready engineers: Transforming maritime education - Tri Cahyadi; W. Winarno; April Gunawan Malau (Universitas Muhammadiyah Malang, 2025)
The maritime industry faces rapid technological advancements and growing sustainability demands, necessitating a workforce that excels not only in technical expertise but also in leadership and management. Despite advancements in maritime education, gaps persist in aligning curricula with industry expectations, particularly in equipping graduates with practical leadership capabilities and advanced management skills. These competencies are critical for addressing complex operational challenges, fostering team collaboration, and ensuring compliance with evolving global regulations. This research contributes to maritime education by focusing on the integration of leadership and management training into engineering programs. It goes beyond traditional technical instruction to propose a competency-based framework that balances technological adaptation with leadership development. Through a qualitative methodology involving interviews with maritime professionals, educators, and graduates, the study examines the extent to which current education meets the demands of the industry and explores strategies to enhance workforce readiness. Findings reveal that while educational programs provide a solid theoretical foundation in technical skills, they fall short in preparing graduates for managerial roles. Only 58.75% of graduates expressed confidence in their leadership capabilities, reflecting the limited emphasis on decision-making, team coordination, and resource management in training programs. Practical exposure to management scenarios is minimal, further hindering the readiness of future leaders. This research emphasizes the urgency of modernizing curricula to include experiential learning in leadership and management. Strengthening collaboration between academia and industry is pivotal to co-developing relevant training programs that address operational complexities. By implementing these strategies, maritime education can cultivate a generation of skilled leaders capable of driving efficiency, innovation, and sustainability in the sector.